Differential Impairment of Interferon-γ Responses in Two Cases of Pulmonary Nontuberculous Mycobacterial Disease. (16th November 2016) - Rae, William; Gao, Yifang; Eren, Efrem; Döffinger, Rainer; Marshall, Ben; Williams, Anthony P.
Abstract : Nontuberculous mycobacteria (NTMs) are weakly virulent intracellular pathogens that are common in food and water supplies. The persistent culture of these organisms in the setting of clinical infection warrants investigation of immune function. In cases of isolated pulmonary NTM (PNTM) disease, underlying immune defects have not been clearly identified. We present two patients with isolated PNTM infection who demonstrated differentially impaired IFN- γ production across a range of stimuli. These cases show that cellular IFN- γ responses may be defective in a proportion of patient suffering PNTM disease and that when assessing responses, the stimulant used in the testing is important to delineate defective cell populations. Impaired IFN- γ responses to IL-12 + BCG seem to be a poor prognostic indicator in PNTM disease and in these cases were not improved by adjuvant IFN- γ .